Sistem Informasi Akuntansi Pengelolaan Iuran dan Buku Kas Pada PDU Kelurahan Pabuaran - Imam; Ubaidillah Ubaidillah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2022)
This research is intended to develop an accounting information system in the management of waste fees and cash books at the Recycling Center (PDU) of Pabuaran Village. The accounting information system can provide convenience in managing finances originating from waste contributions by PDU officers. By using an information system, data management of contributions and cash transactions can be more effective, efficient and certainly more accurate when compared to the manual method. Transaction data that is processed includes transactions for receipt of fees from collector officers, transactions for cash receipts and transactions for cash disbursements. The accounting information system was developed using the waterfall method. The information system is a web-based application developed using the PHP programming language and MySQL database